Combating Bovine Mastitis in the Dairy Sector in an Era of Antimicrobial Resistance: Ethno-veterinary Medicinal Option as a Viable Alternative Approach - Ajose, Daniel Jesuwenu; Oluwarinde, Bukola Opeyemi; Abolarinwa, Tesleem Olatunde; Fri, Justine; Montso, Kotsoana Peter; Fayemi, Omolola Esther; Aremu, Adeyemi Oladapo; Ateba, Collins Njie (Frontiers in Veterinary Science, 2022)
Bovine mastitis (BM) is the traditional infectious condition in cattle rearing, which may result in serious repercussion ranging from animal welfare to economy. Due to high costs associated with preventative and therapeutic expenditures, lower milk output, and early culling, bovine mastitis is accountable for the majority of the financial losses in cattle farming. Streptococcus agalactiae, Staphylococcus aureus, Streptococcus dysgalactiae and coliform bacteria are the predominant pathogens for bovine mastitis. In addition, the occurrence of mastitis has been linked to lactation stage and poor management such as housing conditions udder hygiene. BM is found all throughout the world, with varying rates of Streptococcus agalactiae, in different regions. Despite the fact that modern techniques like appropriate milking practices and less pathogen vulnerability may help to prevent the development of the disease, BM treatment is primarily reliant on antibiotics, for both prophylactic and therapy. Nevertheless, as a result of the proliferation of bacterial agents to withstand antibiotic effects, these therapies have frequently proven ineffectual, resulting in a persistent BM. Consequently, alternative medicines for the management of udder inflammation have been researched, notably natural compounds derived from plants. This review focuses on bovine mastitis in terms of risk factors, pathogenesis, management, molecular identification of causative agents as well as the application of ethnoveterinary medicine as an alternative therapy for bovine mastitis.